The Analysis of Students’ Learning Style Preferred by Basic Listening Classes of English Department at Universitas Negeri Padang - Juliance Primurizki; Aryuliva Adnan; Don Narius (Journal of English Language Teaching, 2020)
The variation of students in acquiring and understanding knowledge is influenced by learning styles. But, based on the observation, the students are less aware of their own preferences in learning styles. This research was conducted to analyze the learning styles preferred by students in the Basic Listening classes of English Department, Universitas Negeri Padang (UNP). This descriptive research used a quantitative descriptive method. The research instrument was questionnaires. There were 2 questionnaires used in this research. First VARK questionnaire (Version 7.8) designed by Fleming. VARK questionnaire represented visual (V), aural (A), read/write (R), and kinaesthetic (K). It consisted of 16 questions with four options. The second questionnaire was Index of Learning Styles (ILS) designed by Richard M. Felder and Barbara A. Soloman in 1997. This questionnaire was categorized into four dimensions, namely active or reflective, visual or verbal, sensitivity or intuition, and sequential or global. It consisted of 44 questions with 2 options. The population of this research was the students in Basic Listening Classes of English Department. The sample was 60 students who were chosen randomly from the total population using Simple Random Sampling. This result of this research showed that the students had various learning styles and mostly their learning styles were dominated by visual style.